The Prevalence of Pinworm Infection in Children of District Mardan, Khyber Pakhtunkhwa, Pakistan - Ullah, Wasia; Nasir , Abdul; Izaz, Muhammad; Rabia (Indus Journal of Bioscience Research, 2025)
The aim of this study was to determine the Enterobius vermicularis prevalence in Khyber Pakhtunkhwa's (KP) Mardan district. Five months, from December 2012 to April 2013, were used to gather the data. For the research, 140 kids between the ages of 1 and 14 were chosen at random. Enterobiasis was detected in stool samples by the direct smear technique. The findings of this study revealed that 27% (38/140) (p